The legal authority and custody of the children, in the cases of separation and divorce, according to the Spanish law and jurisprudence - Guzmán Pérez, Cristina (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
In the cases of marriage separation and civil divorce, the legal authority and the care and the shared custody of the children is frequently controversial and it entails the canonical regulation about the catholic education of the children and their preparation to receive the sacraments of the Christian initiative. A synthesis of the Spanish civil doctrine and jurisprudence is put forward and the reasons to prefer certain judicial options are given, ever bearing in mind the children’s good. Additionally the canonical regulation to be borne in mind is referred to.